(untitled) (BSAA arte, 2020)
Based on a detailed on-site analysis of the architecture built in the monastery of San Julián de Samos (Lugo, Spain) during the 17th and 18th centuries, this paper explores the variability of the structures used to cover the new monastic spaces and its clear lack of stylistic relation with the artistic mainstream and other coetaneous artworks, which were built during the same period in other Galician monasteries. Our last goal is to understand the reasons behind the use of old arched structures when new architectonical styles were being introduced. The role of the Brother Pedro Martínez, from the monastery of San Pedro de Cardeña in Burgos, is revealed here as a key factor.